2020
DOI: 10.1186/s12884-020-03438-1
|View full text |Cite
|
Sign up to set email alerts
|

Attitudes and beliefs in Swedish midwives and obstetricians towards obesity and gestational weight management

Abstract: Background Gestational weight interventions are important in maternity care to counteract adverse pregnancy events. However, qualitative findings indicate potential obstacles in the implementation of interventions due to the sensitivity of the subject and existing obesity stigma. Pregnant women have reported disrespectful or unhelpful communication, while some midwives seem to avoid the topic, as not to upset women. This descriptive study aimed to provide knowledge about maternity care providers’ beliefs about… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(21 citation statements)
references
References 28 publications
2
19
0
Order By: Relevance
“…We found that among such obesity-associated factors, those relating to intrauterine overnutrition including excessive GWG contributed strongly to higher-than-normal BMI growth during the “plastic phase” of the first 2 years. Indeed, there is a need for women with obesity to be provided with more customized advice on dietary intake and physical activity to optimize gestational weight management [ 24 , 79 ]. For the subsequent time period of the preschool years, gestational smoking emerged as a relevant modulator of growth in offspring exposed to obesity in pregnancy in our study.…”
Section: Discussionmentioning
confidence: 99%
“…We found that among such obesity-associated factors, those relating to intrauterine overnutrition including excessive GWG contributed strongly to higher-than-normal BMI growth during the “plastic phase” of the first 2 years. Indeed, there is a need for women with obesity to be provided with more customized advice on dietary intake and physical activity to optimize gestational weight management [ 24 , 79 ]. For the subsequent time period of the preschool years, gestational smoking emerged as a relevant modulator of growth in offspring exposed to obesity in pregnancy in our study.…”
Section: Discussionmentioning
confidence: 99%
“…Causal factors of weight stigma in healthcare have included receiving judgement about excessive weight gain, getting generic advice about being physically activity and eating well, and sensing healthcare provider discomfort when having weight-related conversations [ 39 ]. Studies that have explored perspectives of maternal healthcare providers caring for patients who have obesity confirm that there is discomfort when measuring or discussing weight [ 23 , 40 ]. Interestingly, guidelines for GWG management and obesity in pregnancy largely ignore the potential role weight stigma may have on patient experience, and do not suggest evaluating or caring for WBI [ 19 ].…”
Section: Discussionmentioning
confidence: 99%
“…Of the 34 included studies, 26 studies used a qualitative study design and six studies were quantitative studies. 2,5,6,[59][60][61] One study was a survey with a qualitative data collection method, 62 and one was a framework synthesis of newsprint media. 31 The majority of the studies (n = 24) included either preconception, pregnant, or postpartum women as study participants, 2,5,6,33,34,36,38,39,41,42,[44][45][46][47][48][49][50][51][54][55][56][57]62,63 investigating perspectives of weight stigma either cross-sectionally or retrospectively.…”
Section: Characteristics Of Included Studiesmentioning
confidence: 99%
“…31 The majority of the studies (n = 24) included either preconception, pregnant, or postpartum women as study participants, 2,5,6,33,34,36,38,39,41,42,[44][45][46][47][48][49][50][51][54][55][56][57]62,63 investigating perspectives of weight stigma either cross-sectionally or retrospectively. Six studies included health professionals, 37,40,52,58,59,61 and three studies included both preconception, pregnant, or postpartum women and health professionals. 35,53,60 Two studies reviewed news articles for weight stigma focused on pregnant or postpartum women living with obesity 6,31 (Table S8).…”
Section: Characteristics Of Included Studiesmentioning
confidence: 99%